Herbicidal bio-assay of isocladosporin enantiomers and determination of its plausible absolute configuration - Mankad, Yash; Das, Pronay; Pathan, Ejaj; Deshpande, V. M.; Reddy, D. Srinivasa (Journal of Antibiotics, 2021)
A fungal metabolite, isocladosporin was isolated from natural fungus, Cladosporium cladosporioides in the mid of 90s. Due to the lack of optical rotation of isolated natural product sample, the absolute configuration of the natural product remained undetermined for more than two decades. Herein, we demonstrated an SAR study of enantiomers of isocladosporin in herbicidal bio-assay against wheat coleoptile. Using this study as a comparative tool we further proposed the plausible absolute configuration of natural isocladosporin for the first time. The assigned configuration was also supported through biogenetic precursors.